Mindfulness i svenska kontexter - Plank, Katarina (Religionsvidenskabeligt Tidsskrift, 2015)
ENGLISH ABSTRACT: Mindfulness can be found in three distinctly different settings in Sweden: therapeutic, commercial and religious. Its greatest expansion can be found within in the Swedish health care system, where mindfulness-based therapies and interventions can be used, and among private operators selling mindfulness courses to both public and private sectors. Here, mindfulness is decontextualised and detraditionalised and presented as a universal life-skill without any religious belonging. Although with a difference: the therapeutic use of mindfulness encourages the individual to delevop metacognition and the ability of decentering, while the commercial use of mindfulness puts greater emphasis to sensory experiences. In the religious context, sati (the Pali term translated into mindfulness) is an integral part of a Buddhist soteriologiskt system aiming at freeing the individual from worldly bonds. This shift in conceptualising mindfulness reflects a general trend in Western countries where spirituality replaces religion. SVENSK RESUMÉ: Mindfulness återfinns i tre distinkt olika sammanhang i Sverige: terapeutiska, kommersiella och religiösa. Sin största spridning har mindfulness fått i sekulära och nyreligiösa former som återfinns inom svensk sjukvård där mindfulnessbaserade terapier integrerats i behandlingar och hos privata aktörer som säljer mindfulnesskurser till både offentlig och privat sektor. Här har mindfulness avkontextualiserats och presenteras som en allmänmänsklig färdighet utan kopplingar till religion, dock med skillnaden att det terapeutiska användandet tycks syfta till att individen utvecklar decentrering och metakognition, medan det kommersiella användandet i större grad betonar sinnesupplevelser. I religiösa sammanhang utgör sati (palitermen som kommit att översättas med engelskans mindfulness) en integrerad del i ett soteriologiskt system som syftar till att individen frigör sig från världsliga bindningar. Begreppsglidningen reflekterar en generell utveckling i västerländska länder där andlighet ersätter religion.